2019
DOI: 10.1161/hypertensionaha.118.12437
|View full text |Cite
|
Sign up to set email alerts
|

Proteasome Levels and Activity in Pregnancies Complicated by Severe Preeclampsia and Hemolysis, Elevated Liver Enzymes, and Thrombocytopenia (HELLP) Syndrome

Abstract: Excessive accumulation of misfolded proteins was recently demonstrated in preeclampsia. We examined levels and activity of circulatory proteasome and immunoproteasome (inflammatory subtype) in preeclampsia and hemolysis, elevated liver enzymes, and thrombocytopenia (HELLP) syndrome. We analyzed samples from women with hypertensive pregnancy disorders (n=115), including preeclampsia with severe features (sPE) and HELLP syndrome, and normotensive controls (n=45). Plasma proteasome and immunoproteasome immunoreac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 55 publications
0
9
0
Order By: Relevance
“…(Shang & Taylor, 2011). Plasma proteasome and immunoproteasome are significantly upregulated in PE and hemolysis, elevated liver enzymes, and thrombocytopenia syndrome (Berryman et al, 2019). Sun et al analyzed the gene expression profile of peripheral blood of patients with PE using gene microarray technology, and found that the expression of PSMC5 was increased (Sun et al, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…(Shang & Taylor, 2011). Plasma proteasome and immunoproteasome are significantly upregulated in PE and hemolysis, elevated liver enzymes, and thrombocytopenia syndrome (Berryman et al, 2019). Sun et al analyzed the gene expression profile of peripheral blood of patients with PE using gene microarray technology, and found that the expression of PSMC5 was increased (Sun et al, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…One example is the analysis of blood or bone-marrow derived samples of patients with multiple myeloma to determine response to treatment with approved proteasome inhibitors, and development of resistance [ 45 , 46 , 47 ]. Other studies analyzed blood plasma or bronchioalveolar lavage for an altered amount and activity of extracellular proteasomes as a potential biomarker for acute clinical conditions such as preeclampsia, burn injury, acute ischemic stroke, and acute respiratory stress syndrome [ 48 , 49 , 50 , 51 , 52 ]. Large scale population-based studies on intracellular proteasome activity in circulating lymphocytes, however, are missing.…”
Section: Introductionmentioning
confidence: 99%
“…Since the 20S proteasome is the only proteasome form found in blood [23], a small molecule ratio-based regulatory mechanism may be essential for the proteostasis of the entire organism. Indeed, changes in extracellular proteasome levels were observed during preeclampsia, cancer, and neurodegenerative diseases [24,25]. Interestingly, the role of ATP/Mg 2+ balance in the context of proteostasis maintenance might be supported by studies reporting decreased levels of Mg 2+ in the brain and cerebrospinal fluid associated with neurodegenerative diseases, including Alzheimer's and Parkinson diseases, as well as with aging [26,27].…”
Section: Resultsmentioning
confidence: 99%